Effect of Penetration Enhancers on Transdermal Delivery of Oxcarbazepine, an Antiepileptic Drug Using Microemulsions - Amitkumar Virani; Vinam Puri; Hana Mohd; Bozena Michniak-Kohn (MDPI AG, 2023)
Oxcarbazepine (OXC) is an anticonvulsant drug, indicated for the treatment of the neurological disorder, epilepsy. The objective of the present study was to evaluate the transdermal delivery of OXC from microemulsions using different penetration enhancers. Transcutol® P (TRC), oleic acid (OA), cineole (cin), Labrasol (LS), Tween 80 (T80) and N-Methyl-Pyrrolidone (NMP) were used as penetration enhancers as well as microemulsion components. Simple formulations of OXC in propylene glycol (PG) incorporating various penetration enhancers and combination of penetration enhancers were also evaluated for transdermal delivery. Drug delivery and penetration enhancement were studied using human cadaver skin on Franz diffusion cells. The results showed that all penetration enhancers improved the rate of permeation of OXC compared to the control. The flux of drug delivery from the various formulations was found to be, in decreasing order, cin > OA + TRC > NMP > TRC > OA. Overall, microemulsions prepared using cineole, Tween 80 and Transcutol® P (TRC) were shown to be provide the best penetration enhancement for OXC.